CONDITION OF SANITATION FACILITIES AT MOJOSARI TRADITIONAL MARKET, MOJOKERTO - Ervin Wahyuning Maulidah; Bambang Sunarko; Sri Mardoyo (GEMA LINGKUNGAN KESEHATAN, 2013)
Community health status was also determined by environmental condition, thatincluded public places and availability of health services. Among many problems encounteredby the Mojosari Market included the fact that many merchants disposed off their garbageindescriminately, dirty and smelly bathrooms and toilet rooms, smelly and tarnish placereserved for praying and a place for selling birds, and the so called clean water that deviatedfrom standards. This research was directed to assess condition of sanitation facilities inMojosari Market in 2013.This was classified as a descriptive observational research following a cross sectionalapproach. Data collection is conducted by means of interviews, observation and laboratorytests. Object of this investigation were condition of sanitation facilities as well as otherfacilities. Data was analyzed descriptively.Results indicated that clean water availability was granted with score of 400 (40%)which meant it was in compliance, bath room and toilet room was granted with score of 500(50%) which also meant it was in compliance, garbage disposal facility was given a score of620 (62%) meaning that it was in compliance, sewerage system scored 200 (20%) and itcomplied to the expected requirements, the musholla scored 240 (40%) and remained incompliance, bird selling place scored 272 (34%) which was in compliance range while thehealth service post scored 0 and it did not domply to the requirement.It was deemed advisable to carry out clean water disinfect at the sources, to addartflclal lighting units in toilet room and to remove and clean all visible crusts, to incorporatesorting mechanism in garbage disposal and to provide cover on garbage containers, cleaningthe sewer system, periodical cleaning at musholla , and to provide health service postequipped with first aid items.Key words: sanitation facilities and other facilities